1998
DOI: 10.1034/j.1600-0420.1998.760302.x
|View full text |Cite
|
Sign up to set email alerts
|

Optic disc size and retinal vessel characteristics in healthy children

Abstract: ABSTRACT.Purpose: To characterize the optic disc and retinal vessels in healthy children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
3
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 38 publications
(61 reference statements)
3
54
3
1
Order By: Relevance
“…However, the cupping of the disc is known to be increased in periventricular leukomalacia. Another study of 100 healthy children and adolescents revealed the median optic disc area to be 2.67 mm 2 , in subjects ages 3 to 19 years [30]. In another study the mean disc area was 2.49 mm 2 in healthy and glaucomatous eyes [31].…”
Section: Subjects With Albinism Controls P-valuementioning
confidence: 99%
See 1 more Smart Citation
“…However, the cupping of the disc is known to be increased in periventricular leukomalacia. Another study of 100 healthy children and adolescents revealed the median optic disc area to be 2.67 mm 2 , in subjects ages 3 to 19 years [30]. In another study the mean disc area was 2.49 mm 2 in healthy and glaucomatous eyes [31].…”
Section: Subjects With Albinism Controls P-valuementioning
confidence: 99%
“…The age of the controls was greater compared with the patients with albinism. However, Hellstrom et al [30] found no change in the size of the disc, cup or rim with increasing age. In addition, we could not reliably use the ratio of disc diameter to distance of the optic nerve to the macula, used in other studies of optic nerve hypoplasia, due to the difficulty in defining the center of the foveal avascular zone in albinism.…”
Section: Subjects With Albinism Controls P-valuementioning
confidence: 99%
“…Detailed data for these children and adolescents are presented elsewhere. 13 The study was approved by the Committee for Ethics at the Medical Faculty, Goteborg University. Informed consent was obtained from the parents after the nature of the procedures had been fully explained.…”
Section: Reference Groupmentioning
confidence: 99%
“…Therefore, each child requires individual assessments of multiple Areas of the optic disc, the cup and the neuroretinal rim of the patients in relation to reference material from fullterm healthy children.The shaded area depicts the fifth and 95th percentiles of a reference material. 20 aspects of vision. 34,35 There is evidence that some difficulties related to prematurity disappear with age.…”
Section: Discussionmentioning
confidence: 99%